DESOD: a mathematical programming tool to optimally design a distributed energy system. (1st April 2016) - Bracco, Stefano; Dentici, Gabriele; Siri, Silvia
Abstract: One of the main challenges of the community is nowadays to satisfy end use energy demand in an eco-friendly and economic way. EU governmental policies encourage the spread of efficient and clean technologies in the energy sector, supporting distributed generation, cogeneration and trigeneration, as well as the exploitation of renewable sources. Furthermore, smart microgrid and energy storage systems have acquired more and more importance in the last years. Within this context, the DESOD (Distributed Energy System Optimal Design) tool, described in the present paper, has been developed at the University of Genoa. DESOD is based on a mixed-integer linear programming model to optimally design and operate a distributed energy system which provides heating, cooling and electricity to an urban neighborhood. In the paper, the model is described in detail and the results derived from its application to a real test case are discussed; a computational analysis of the model is reported as well. Highlights: A mathematical programming tool to optimally design a distributed energy system. Mixed-integer linear programming model. Use of CHP units, photovoltaics, heat pumps, chillers and storage systems. Application to a real test case in the North of Italy.